O pensamento político estoico e a idealização do governo de Marco Aurélio - Onesko, Stéfani de Almeida (2017)
Our research seeks to understand the construction of the ideal of a good leader around the emperor?s figure Marcus Aurelius (A.D. 121 - 180 A.D.) in the period in which he remained in power (161 A.D. - 180 A.D.). The emperor adopted the Stoic philosophy as moral conduct and reflected in his writings the concern in adjusting to the precepts of this doctrine that intended to direct the man and the leader in the way of virtus, especially clementia, iustitia, moderatio and pietas. From the relations between Stoicism and Imperium we sought to demonstrate that, although there was no systemic opposition of Stoicism to the imperial political model, it defined the criteria that established the difference between the optimus princeps and the tyrannus. Our study was carried out through the discussion in contemporary historiography about the Roman philosophy and political institutions. The source selected was the work Meditations written by the emperor which involves the production of personal notes by means of the writing style hypomnemata, in the ancient Roman world